Ответы и объяснения

  • Участник Знаний
2013-11-29T21:49:45+00:00
1а)5 \sqrt{2} +23*3 \sqrt{3} -7 \sqrt{2} =69 \sqrt{3} -2 \sqrt{2}
б)4*3+9=12+9=21
2) \sqrt{1/4*28} = \sqrt{7}
 \sqrt{1/9*54} = \sqrt{6}
1/2 \sqrt{28} >1/3 \sqrt{54}
3a) \sqrt{5} ( \sqrt{2} + \sqrt{5} )/ \sqrt{2} ( \sqrt{2} + \sqrt{5} )= \sqrt{5} / \sqrt{2} = \sqrt{10} /2
b) \sqrt{a} ( \sqrt{a} -3)/3( \sqrt{a} -3)= \sqrt{a} /3
4a)7 \sqrt{21} /2*21= \sqrt{21} /6
b)2)22( \sqrt{13} + \sqrt{2} )/13-2=)22( \sqrt{13} + \sqrt{2} )/11=)22( \sqrt{13} + \sqrt{2} )
5)(3- \sqrt{15} +3+ \sqrt{15} )/(3+ \sqrt{15} )(3- \sqrt{15} )=6/(9-15)=6/(-6)=-1